The applicability aspects of medical marijuana in Poland - Artur Owczarek; Paweł Kozaczuk; Bożena Grimling; Bożena Karolewicz Karolewicz (Polish Pharmaceutical Society, 2023)
Background: Cannabis has been used medicinally for centuries. Historically, cannabis-based medicines have been used to treat many conditions. In the 20th century, their use was criminalized worldwide. Nowadays, many countries decriminalize their use. The complexity of the subject and the qualitative variability of the active factors of individual varieties of this species determine new areas that require research and analysis. Attention is drawn to legal issues, quality control issues, and shortages of randomized and controlled clinical trials. The article is addressed to health care professionals and people interested in legal and medical aspects and the potential benefits and challenges related to medical cannabis. Aim of the study: The aim of article analyzed the legal and practical aspects of access to marijuana and its use for medical application in Poland. Materials and method: Comparing legal solutions and analyzing differences in the regulations of marijuana used for medical purposes in selected countries will also make it possible to indicate the directions of development in this area in Poland. Results: This article discusses the legal framework for access to medical cannabis and its use for medical purposes. There are at least twenty-one types of raw materials on the market in Poland, which, while maintaining the same levels of THC and CBD, differ in their terpene profile and, therefore, in detailed therapeutic properties. Understanding the differences can enable pharmacists to support and monitor patient drug therapy in this area. The area of medical use of cannabis was also presented in terms of the possibility of cooperation between physicians and pharmacists in providing services to patients in order to achieve therapeutic effectiveness and develop risk management tools for pharmacotherapy using medical marijuana. Conclusions: As limitations in research and use are eliminated, new therapeutic options will be explored. Despite numerous challenges and limitations related to the use of Cannabis, such as the problems of raw material selection, quality control, stability, safety and effectiveness, the achievements so far in this area should be considered encouraging and important for the health care system in Poland.